Product quality, product price, and share dynamics in the German compact car market - Uwe Cantner; Jens J. Krüger; René Söllner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
The present paper examines one of the central elements of evolutionary thinking - competition formalized by the replicator dynamics mechanism. Using data on product characteristics of automobiles sold on the German domestic market over the period 2001-2006, we construct a competitiveness or fitness variable for each car model applying non-parametric efficiency measurement techniques. The basic question we intend to answer is whether cars providing a higher quality-price ratio for consumers tend to increase their market share compared to variants with lower quality-price ratios. The relationship between a car models' fitness and its market performance is empirically tested in a regression framework. The results show that the principle of `growth of the fitter' is working as suggested by evolutionary theory. In particular, we find that car models with considerably lower fitness than the market average lose, whereas models with above-average fitness gain additional market shares.
Keywords: O33; D12; L15; 330; Replicator Dynamics; Product Characteristics; Data Envelopment Analysis; Personenkraftwagen; Produktqualität; Data-Envelopment-Analyse; Preiswettbewerb; Evolutionsökonomik; Marktanteil; Schätzung; Deutschland